2011
DOI: 10.1016/j.appet.2011.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive deficits in obese persons with and without binge eating disorder. Investigation using a mental flexibility task

Abstract: Objective: Studies suggest that cognitive deficits and attentional biases play a role in the development and maintenance of obesity and eating disorders. In this study, we simultaneously examine attentional biases, as well as inhibitory control and mental flexibility, which are keys to controlling unwanted behaviors and thoughts in obese patients with and without binge eating disorder. Methods: 16 obese patients with binge eating disorder and 16 patients without binge eating disorder were compared with 16 norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
145
0
13

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(172 citation statements)
references
References 49 publications
14
145
0
13
Order By: Relevance
“…In 2011, a study evaluated these functions in obese patients with BED, without BED and people with normal weight, and concluded that obese participants had significantly more errors of commission (pressing keys in response to any stimulus) and more errors of omission (not pressing keys when a target was visible) than those in the control group. In addition, the study showed that obese participants with BED had significantly more errors and omissions that those without the disorder (35). The results from Mobbs et al are consistent with the present study, in which obese patients presented deficits in general inhibitory control and difficulty in relation to selective attention.…”
Section: Score Medium Without Bedsupporting
confidence: 82%
See 1 more Smart Citation
“…In 2011, a study evaluated these functions in obese patients with BED, without BED and people with normal weight, and concluded that obese participants had significantly more errors of commission (pressing keys in response to any stimulus) and more errors of omission (not pressing keys when a target was visible) than those in the control group. In addition, the study showed that obese participants with BED had significantly more errors and omissions that those without the disorder (35). The results from Mobbs et al are consistent with the present study, in which obese patients presented deficits in general inhibitory control and difficulty in relation to selective attention.…”
Section: Score Medium Without Bedsupporting
confidence: 82%
“…With BED which in turn play a role in the development and maintenance of obesity and eating disorders (35). In 2011, a study evaluated these functions in obese patients with BED, without BED and people with normal weight, and concluded that obese participants had significantly more errors of commission (pressing keys in response to any stimulus) and more errors of omission (not pressing keys when a target was visible) than those in the control group.…”
Section: Score Medium Without Bedmentioning
confidence: 99%
“…Unlike individuals with BED, those with BN additionally engage in compensatory behaviors (e.g., vomiting) in order to prevent weight gain. Some studies found greater delay discounting or poorer response inhibition in obese adults compared to normal-weight individuals (Mobbs, Iglesias, Golay, & Van der Linden, 2011;Nederkoorn, Smulders, Havermans, Roefs, & Jansen, 2006;Weller, Cook, Avsar, & Cox, 2008) or in adults with BED or BN compared to controls (Manwaring, Green, Myerson, Strube, & Wilfley, 2011;Rosval et al, 2006;Wu et al, 2013). These findings, however, are contrasted by a number of studies that did not find differences in delay discounting or response inhibition between those groups (Claes, Mitchell, & Vandereycken, 2012;Claes, Nederkoorn, Vandereycken, Guerrieri, & Vertommen, 2006;Galimberti, Martoni, Cavallini, Erzegovesi, & Bellodi, 2012;Hendrick, Luo, Zhang, & Li, 2012;Loeber et al, 2012;Nederkoorn et al, 2006;Van den Eynde et al, 2012;Wu et al, 2013).…”
Section: Introductionmentioning
confidence: 60%
“…In addition, in the go/no-go task we found faster reaction times in response to the presentation of food-associated compared with neutral stimuli for both groups. Interestingly, there are two studies that used a go/no-go task with food-associated (as well as body related) and neutral words to investigate inhibitory control in bulimics 23 and patients with binge eating disorder 29 and also found that all participants tended to respond faster to foodassociated compared with neutral stimuli. Thus, these results suggest that not only obese, but also normal-weight controls show an approach bias for food-associated stimuli.…”
Section: Discussionmentioning
confidence: 99%